Seasonal Variation of Phytoplankton in AL-Diwaniya River - I. Yousif, Malath; S. A. Aldhamin, Ahmed (Iraqi Journal of Science, 2023)
This study was conducted from January to October 2014, the samples werecollected monthly from four stations in AL-Diwaniya River at AL-Diwaniya city.Phytoplankton species which are diagnosed during study period are (506) and thenumbers of common types in four sites are (61). Bacillariophyceae is dominate onother classes and Chlorophyceae, Cyanophyceae, Dinophyceae then Chrysophyceaeand Euglenophyceae. The study shows that there are (150), (144), (118) and (94)species in the first, second, third and fourth sites. The species that have highs numbersare (Achnanthes, Cymbella, Nitzschia, Navicula). Other types are dominant in theirexistence and number during study period (Cycltella comta, Cylotella Ocellata,Cycletella meneghiniana, Cyleotella Kutzingana, Pediastrum somplex, Diatomaelongatum and Cocconeis Placentula) During the study period, there are seasonal andsite changes in total number of phytoplankton which ranged between (440.61-2994.3cell×103/L).